Multi-layer resource configuration and safety optimization for integrated modular avionics with resource sharing and isolation - Hongli Wang; Zhiwei Chen; Xiaotong Fang (PLoS ONE, 2026)
The aviation industry extensively employs integrated modular avionics (IMA) to enhance system efficiency by sharing resources across various functions. Despite the benefits, the design of IMA systems is not without its challenges, particularly in achieving cost-effectiveness, ensuring availability, and addressing safety concerns. Optimizing resource utilization in IMA systems is increasingly complex due to the growing functionality and quantity of resources in aviation modules and technological flexibility. This paper presents a multi-layer resource configuration and optimal design method for IMA systems, with a dual focus on resource sharing and isolation mechanisms (which prevent fault propagation and enhance system safety). Our approach takes into account not only the strategic planning of resource sharing but also the intricacies of isolation scheme design, especially in the context of risk propagation. The architecture of the multi-layer resource configuration is meticulously structured and formalized to account for the unique dynamics of risk propagation across different configurations. The optimization process for the configuration scheme is formalized as a constrained multi-objective optimization problem. An optimal performance configuration scheme for the IMA systems can be identified that requires the minimum amount of resources. Finally, the effectiveness of the proposed method is demonstrated through the presentation of an illustrative example. The results show that the proposed approach effectively balances safety, efficiency, and cost in IMA resource management.